Language Extended Lexicon points : estimating the size of an application using its language - Antonelli, Rubén Leandro
Estimating the size of a software system is a critical task due to the implications the estimation has in the management of the development project. There are some widely accepted estimation techniques: Function Points, Use Case Points and Cosmic Points, but these techniques can only be applied after the availability of a requirements specification. In this paper, we propose an approach to estimate the size of an application previous to its requirements specification by using the application language itself, captured by the Language Extended Lexicon (LEL). Our approach is based on Use Case Points and on a technique which derives Use Cases from the LEL. The proposed approach provides a measure of the application’s size earlier than the usual techniques, thus reducing the effort needed to apply them. An initial experiment was conducted to evaluate the proposal.